The value of ultrasound in diagnosing extracranial large-vessel vasculitis compared to FDG-PET/CT: a retrospective study - Löffler, Christian; Hoffend, Johannes; Benck, Urs Tobias; Krämer, Bernhard; Bergner, Raoul (Clinical rheumatology, 2017)
Large-vessel vasculitis (LVV) is a group of diseases mainly comprised of giant-cell arteritis (GCA), Takayasu arteritis, and a series of rare diseases like Behçet’s disease, IgG4-related disease, infectious aortitis, and other unfrequent entities. Besides clinical and laboratory features, Doppler sonography (DS) can assist in establishing the diagnosis. Its diagnostic sensitivity has been evaluated in various studies, most of them, however, in temporal arteritis (TA) respectively in LVV with involvement of the temporal artery. Little is known in extracranial LVV. We retrospectively evaluated the diagnostic accuracy of DS in 30 patients with extracranial, non-temporal LVV using the highly sensitive PET/CT as method of reference in comparison to 20 controls who were found to have no LVV. We investigated ten arterial sites and documented the presence of the sonographic halo sign. Sensitivities of DS for LVV were highest in the subclavian and axillary arteries (71.4%/72.2%) and low in the abdominal aorta (26.1%) and the common femoral artery (16.7%). DS detected 24 out of 30 cases of LVV (overall sensitivity 80.0%). The LVV cases where DS was completely negative did not significantly differ in leukocyte count, C-reactive protein, or erythrocyte sedimentation rate from LVV cases with positive DS. DS is a potent method in diagnosing extracranial LVV especially in the axillary and the subclavian arteries. Aortic, intraabdominal, and lower extremity artery manifestations, however, are often missed by DS. A second imaging modality (e.g., PET/CT) is therefore required.
Published online: 15 May 2017
Gesehen am 20..08.2018